Strategi Kepala Sekolah dalam Meningkatkan Kinerja Guru di SMP IT Qurrata A’yun - Efrimul Yanti; Asmendri Asmendri; Muhammad Yusuf Salam (STKIP PGRI SITUBONDO, 2023)
The principal is the main factor in managing educational institutions in order to realize the goals of education itself. The main problem in this research is what the strategy of the principal of SMP IT Qurrata A’yun in improving teachers performance. Data processing is carried out in a qualitative descriptive manner, which is obtained through observation, interviews and documentation. The role of the principal of SMP IT Qurrata A’yun by using a democratic leadership style, so that the principal can mobilize teachers in carrying out school programs and can achieve the goals that have been set. The principal’s strategy of SMP IT Qurrata A’yun in improving teacher performance are by conducting performance coaching for teachers, conducting supervision, fostering teacher discipline, providing motivation and giving awards